(untitled) (Research, Society and Development, 2022)
Introduction: Currently, plant-based diets have gained more and more supporters of this lifestyle, aiming for a healthier diet. In the sports environment, many athletes are adopting this food practice and thus end up generating several debates if this type of food offers all the nutrients an athlete needs. Athletes who follow a vegetarian pattern can meet their protein needs through plant sources, when a wide variety of this food is included daily in the diet and energy intake is adequate. Nutrients to watch out for to avoid nutritional deficiencies in vegetarian athletes include protein, n-3 fatty acids, iron, zinc, calcium, iodine, vitamin D and vitamin B12. This work gathers scientific evidence from 2012 to 2022 that addresses food and nutritional needs in vegetarian athletes and aims to discuss their main nutritional deficiencies, energy needs and impact on performance. Based on these studies, the vegetarian diet pattern does not negatively affect the athletes’ performance and their nutritional needs are easily met when properly planned.